Ralph Ellison and the raft of hope : a political companion to Invisible man - Morel, Lucas E., 1964- (University Press of Kentucky, 2004)
"Ellison's relevance as a political novelist, essayist, and commentator did not end with the publication of Invisible Man or as the civil rights movement waned. This collection of essays demonstrates that Invisible Man deserves its place in the pantheon of great American novels and that Ellison should be regarded as an essential framer of recent American political thought. His conception of America's basic democratic project - strangers, bound together by common citizenship, crafting a vision for America's future and forging consensus on the path toward that goal - is especially valid in the new century as the nation struggles with divisions and contradictions unimagined during Ellison's lifetime." "The essays in Ralph Ellison and the Raft of Hope probe the political lessons of the landmark novel Invisible Man, in which Ellision reflects on the sacred ideals that set the American republic into motion."--Jacket